Outcomes of beta blocker use in cocaine-associated chest pain: a meta-analysis. Issue 9 (19th June 2018) - Pham, Don; Addison, Daniel; Kayani, Waleed; Misra, Arunima; Jneid, Hani; Resar, Jon; Lakkis, Nassir; Alam, Mahboob
Abstract : Objectives: Beta blockers (β-blockers) remain a standard therapy in the early treatment of acute coronary syndromes. However, β-blocker therapy in patients with cocaine-associated chest pain (CACP) continues to be an area of debate due to the potential risk of unopposed α-adrenergic stimulation and coronary vasospasm. Therefore, we performed a systematic review and meta-analysis of available studies to compare outcomes of β-blocker versus no β-blocker use among patients with CACP. Methods: We searched the MEDLINE and EMBASE databases through September 2016 using the keywords 'beta blocker', 'cocaine' and commonly used β-blockers ('atenolol', 'bisoprolol', 'carvedilol', 'esmolol', 'metoprolol' and 'propranolol') to identify studies evaluating β-blocker use among patients with CACP. We specifically focused on studies comparing outcomes between β-blocker versus no β-blocker usage in patients with CACP. Studies without a comparison between β-blocker and no β-blocker use were excluded. Outcomes of interest included non-fatal myocardial infarction (MI) and all-cause mortality. Quantitative data synthesis was performed using a random-effects model and heterogeneity was assessed using Q and I 2 statistics. Results: A total of five studies evaluating 1794 subjects were included. Overall, there was no significant difference on MI in patients with CACP on β-blocker versus no β-blocker (OR 1.36, 95% CI 0.68 to 2.75; p=0.39). Similarly, there was no significant difference in all-cause mortality in patients on β-blocker versus no β-blocker (OR 0.68, 95% CI 0.26 to 1.79; p=0.43). Conclusions: In patients presenting with acute chest pain and underlying cocaine, β-blocker use does not appear to be associated with an increased risk of MI or all-cause mortality.